2008
DOI: 10.1007/s11422-008-9145-6
|View full text |Cite
|
Sign up to set email alerts
|

Socio-scientific reasoning influenced by identities

Abstract: Based on the comments by Lopez-Facal and Jiménez-Aleixandre, we consider that the cultural identities within Europe interfere with the question of the re-introduction of the Slovenian bear, generating a kind of ''discrimination.'' When the SAQs under debate run against the students' systems of value, it seems that the closer the connection between the SAQs (socially acute questions) and the territorial and cultural identity, the more deeply the associated systems of values are affected; and the more the eviden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 1 publication
2
21
0
2
Order By: Relevance
“…These authors also conclude that students' decisions were based on their ability to identify with actors associated with the issue and their pre-existing preferences (if any) for those actors. This result was consistent with previous studies on SSI argumentation (e.g., López-Facal and Jiménez-Aleixandre 2008; Simonneaux and Simonneaux 2009). In keeping with these observations, Zeidler (1997) has concluded that students tend to use information that aligns with their convictions and ignore contradictory evidence, which is also in line with the results of Chang and Chiu (2008), indicating that negative heuristics were often ignored in students' informal argumentation on SSI.…”
Section: Decision-making On Ssisupporting
confidence: 93%
“…These authors also conclude that students' decisions were based on their ability to identify with actors associated with the issue and their pre-existing preferences (if any) for those actors. This result was consistent with previous studies on SSI argumentation (e.g., López-Facal and Jiménez-Aleixandre 2008; Simonneaux and Simonneaux 2009). In keeping with these observations, Zeidler (1997) has concluded that students tend to use information that aligns with their convictions and ignore contradictory evidence, which is also in line with the results of Chang and Chiu (2008), indicating that negative heuristics were often ignored in students' informal argumentation on SSI.…”
Section: Decision-making On Ssisupporting
confidence: 93%
“…This is consistent with previous studies in argumentation (e.g. Kuhn, 1991) but also in socioscientific issues (Author, 2008;Simonneaux & Simonneaux, 2009) who examined how students' personal and cultural identities can affect their discussions of an SSI. These researchers concluded that students project their identities, either personal or cultural, onto the actors in the SSI, and in that way making it is more difficult for them to reason about an issue without their own belief systems influencing their decisions.…”
Section: Students Decide Differently and Provide Different Justificatsupporting
confidence: 91%
“…Even though we know that students' cultural experiences and personal narratives influence their decisions (e.g. Author, 2009;Levinson, 2008;Simonneaux & Simonneaux, 2009), and some studies in argumentation have been conducted across different cultures (i.e. Author, 2010; Kuhn, Wang & Li, 2011), not much is yet known about how students decide about a socioscientific issue they are studying and how different those decisions and justifications might be when comparing diverse populations (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Earlier versions of the model called for opportunities for students to consider the "social connections" of issues as they engage in SSI learning (see Figure 1), but this is one of the more challenging aspects of the approach for many science teachers (Hughes, 2000;Sadler et al, 2006). By referencing "socio-scientific reasoning" which has been unpacked by researchers and practitioners (Herman, 2015;Sadler, Klosterman & Topcu, 2011;Simonneaux & Simonneaux, 2009), we intended to add detail and depth to the suggestion for incorporating social dimensions of issues.…”
Section: Socio-scientific Reasoningmentioning
confidence: 99%